PENGARUH MODEL LATIHAN AGILITY TERHADAP KEMAMPUAN DRIBBLING - Adn Adam; Dadan Muldan; Ramdhani Rahman (Journal of Physical Education and Sport Science, 2020)
The influence of the agility training model on the dribbling ability of the football extracurricular students of SMK Al Jabbar in 2020. Health and Recreation Physical Education Study Program. This study aims to see the effect. This research is a pre-experimental research design, a form of experimental design. The research design used in this study is in the form of One Group Pre test and Posttest Design, the subject of this study is the Football Extracurricular of Al Jabbar Vocational High School which has 25 students. The instrument used to measure dribbling ability is the dribbling test developed by Bobby Charlton (in Danny Mielke, 2007: 8). The results showed that there was a significant effect on the agility training model on the ability to dribble the football extracurricular skills of SMK Al Jabbar by noting a time difference of 5.4 seconds. The conclusion of the study is declared significant if the value of t count> t table and the value of sig <0.05 (Sig <0.05). which means that t is worth 12.392> from t table which is worth 1.71088, therefore Ha is accepted and Ho is rejected.© 2021 STKIP Muhammadiyah Kuningan